Integrating innovative learning assessment approaches in Nigeria’s tertiary education system (2021)
This paper examined the need for integrating innovative learning assessment approaches to improve tertiary education standard in Nigeria arising from the increasing demands for technical competencies, analytical thinking, problem-solving, communication, risk-taking, and entrepreneurial skills. The paper argued that the present adopted learning assessment approaches in Nigeria’s tertiary education system are deficient in producing graduates with these skills. It therefore advocated the need for innovative learning assessment approaches in tertiary education system in Nigeria. It began with a discussion of the requirements of contemporary world of work and the need to prepare tertiary institutions students to acquire such skills. It also dissected the learning assessment approaches in tertiary institutions in Nigeria and extensively discussed the deficiencies inherent in the approaches. The paper recommended various innovative approaches that can be adopted to improve Nigeria’s tertiary education system and concluded that tertiary institutions in Nigeria should integrate these approaches so as to produce graduates who possess skills required in today’s world of work.